B cell and B cell-related pathways for novel cancer treatments. (February 2019) - Tokunaga, Ryuma; Naseem, Madiha; Lo, Jae Ho; Battaglin, Francesca; Soni, Shivani; Puccini, Alberto; Berger, Martin D.; Zhang, Wu; Baba, Hideo; Lenz, Heinz-Josef
Highlights: B cells secrete immunoglobulins, promote T cell response, kill cancer cells directly. B cell and B cell-related pathways play key roles in activating local immune response. In humoral immunity, B cell and B cell-related pathways play the important roles. Recent evidences show the potential role of B cell for novel cancer treatment. Abstract: B cells are recognized as the main effector cells of humoral immunity which suppress tumor progression by secreting immunoglobulins, promoting T cell response, and killing cancer cells directly. Given these properties, their anti-tumor immune response in the tumor micro-environment (TME) is of great interest. Although T cell-related immune responses have become a therapeutic target with the introduction of immune checkpoint inhibitors, not all patients benefit from these treatments. B cell and B cell-related pathways (CCL19, −21/CCR7 axis and CXCL13/CXCR5 axis) play key roles in activating immune response through humoral immunity and local immune activation via tertiary lymphoid structure (TLS) formation. However they have some protumorigenic works in the TME. Thus, a better understanding of B cell and B cell-related pathways is necessary to develop effective cancer control. In this review, we summarize recent evidences regarding the roles of B cell and B cell-related pathways in the TME and immune response and discuss their potential roles for novel cancer treatment strategies.